Economic Considerations in Tree Lopping - Rawat, J. K. (Indian Forester, 1993)
Data obtained from a two year old experiment on lopping in young plantations (ages 5 and 8 years) of Acacia nilotica in semi-arid zone of Haryana have been analysed. Lopping has been found to affect growth rate of trees adversely. However, the effect was found to be significant only in case of heavy lopping (viz. of 2/3 intensity) in 5 year old crop. From economic analysis of this case it is concluded that the capitalised. Value of the lopped material is unable to compensate for the loss in growth of the crop. The extent of loss was estimated to be nearly 10 per cent of the value of the standing biomass.